THE EFFECTS OF LEARNING MATERIALS AND SELF-CONCEPT TOWARDS STUDENTS’ MASTERY ON PASSIVE VOICE - Rezeki, Indah Sri (ENGLISH JOURNAL, 2016)
This research is aimed to find out the effects of learning materials and self-concept towards students‘ mastery on passive voice at private universities in Bogor – West Java. The method used in this research is an experiment method. Number of the samples is 60 second semester students chosen randomly from all second semester students of Ibn Khaldun University, Bogor – West Java. The data collection was done by using library technique, observation and questionnaire distribution. The data analysis was done by using descriptive statistics. This research was conducted from October 2014 until July 2015. The result of the research shows: 1) The students taught by using module have better mastery on passive voice than those taught by using non-module. This is proved by the Significance value 0.003 < 0.05 and Fo 10.010> 2.76. It means that there is a significant effect of learning materials towards students‘ mastery on passive voice. 2) The students with high self-concept have better mastery on passive voice than those with low self-concept. This is proved by the significance value 0.013 < 0.05 and Fo 6.510> 2.76. It means that there is a significant effect of self-concept towards students‘ mastery on passive voice. 3) There is no significant interactive effect of learning materials and self-concept towards students‘ mastery on passive voice. This is proved with Sig. value 0.761 > 0.05 and Fo0.094< 2.76.